CAMPUR KODE DALAM BAHASA INDONESIA PADA ACARA SAMATRA ARTIS BALI DI MEDIA MASSA BALI TV - Lilik Yudiastari, Ni Putu (Humanis, 2016)
This research entitled “campur kode dalam bahasa Indonesia on Samatra Artis Bali show at Bali TV”. There are two problems. That can be analyzed on this research , such as; types of codes and the causes of code mixing which occur on the show. The purpose of research is identify types and factor of code mixing on the Samatra Artis Bali show. To get the goal, using methods and technique.First collecting the data using seeing technique.Such as watching the video.Which is help by teknik simak bebas libat cakap and make the transcript by taking note.Both data analysis process using kualitative descriptive method. The method is descripting the data, such as code mixing and continue with analysis.
Keywords: code mixing, sociolinguistic, and media language